A review on methods of finding losses and cooling methods to increase efficiency of electric machines - Gundabattini, Edison; Kuppan, Ravi; Solomon, Darius Gnanaraj; Kalam, Akhtar; Kothari, D. P.; R. A., Bakar (Ain Shams University, 2021)
Performance of electric motors and losses in terms of heat and temperature are reviewed in this paper. Airgap eccentricity, electromagnetic performance, effect of temperature and losses are shown as factors affecting the efficiency. Several methods of computer aided analyses are listed. Temperature distribution in an induction motor is shown through the results of a simulation. Different cooling methods are reviewed. Future directions for research include cryogenic cooling, heat pipes and usage of phase change materials.